Evaluation of ischemia modified albumin levels in major depression patients - Karaaslan, Özgül; Hacımusalar, Yunus; Amuk, Özge Ceren; Bal, Ceylan (Journal of Surgery and Medicine, 2019)
Aim: Depression is an important public health problem, which has been associated with an antioxidant defense system. Ischemia-modified albumin (IMA) is a new biomarker that measures ischemia. The aim of this study was to evaluate IMA levels as a new parameter related to oxidative stress in patients with major depressive disorder (MDD). Methods: This cross-sectional case-control study included 59 patients aged between 18-65 years who were admitted to our psychiatry outpatient clinic between June 2018-December 2018, diagnosed with MDD and had not used psychotropic drugs for 3 months. In addition, 59 age and sex matched healthy controls were included in the study. Serum IMA and albumin levels were measured in blood samples taken from each patient and from control groups. Hamilton Depression Rating Scale (HDRS) was applied to the subjects to evaluate the depression level. Results: Among the MDD group, 27 patients (45.8%) were male and 32 (54.2%) were female. The number of males and females in the control group were 29 (49%) and 30 (51%). Mean ages of the patients in MDD and control groups were 39.40 (12.20) and 38.67 (9.29) years, respectively. No statistically significant difference was found between the groups in terms of age and gender (P=0.942 and P=0.714, respectively). The mean IMA level of MDD and control group patients were 0.84 (0.39) and 0.82 (0.30), respectively; the difference was statistically significant (P<0.001). There was also a statistically significant difference between the albumin levels of the two groups (P=0.01). Correlation analysis showed a positive correlation between serum IMA levels and HDRS scores (r=0.235, P=0.008). Conclusion: In our study, IMA levels of MDD patients were significantly higher than that of the control group. This result may be an indicator of increased oxidative stress in patients with depression. There is little data in the literature evaluating IMA levels in psychiatric disorders.